Adolescent Attachment: A Social Relations Perspective on Family Relations. Issue 2 (24th May 2021) - De Meulenaere, Jan; Stas, Lara; Antrop, Inge; Buysse, Ann; Lemmens, Gilbert M.D.
Abstract : While attachment at an early age is almost exclusively determined by parental behavior, variation in the quality of attachment in adolescence seems strong to be influenced by the complex interplay between the adolescent's internal working model and its environment. To unravel the different sources of variance in adolescent attachment relationships we applied the Social Relations Model. Two parents and two adolescents from 70 relatively well‐functioning families reported on their attachment relationships within a family context. In this study, attachment was conceptualized by two different dimensions of attachment, namely anxiety (for being abandoned) and avoidance (of intimacy). Our findings suggest adolescents experience little attachment anxiety throughout adolescence, but they report significantly more attachment avoidance toward their parents. The variance in the quality of adolescents' attachment relationships was mainly determined by characteristics of the adolescent and the unique adjustments they make to the attachment figure. Resumen: Si bien el apego en los primeros años de vida está casi exclusivamente determinado por la conducta de los padres, la variación de la calidad del apego en la adolescencia parece significativamente influenciada por la interacción compleja entre el modelo de funcionamiento interno del adolescente y su entorno. Para descifrar las diferentes fuentes de varianza en las relaciones de apego de los adolescentes, aplicamos el modelo de relaciones sociales. Dos padres y dos adolescentes de 70 familias con un funcionamiento relativamente bueno informaron sobre sus relaciones de apego dentro de un contexto familiar. En este estudio, el apego se conceptualizó mediante dos aspectos diferentes del apego, por ejemplo, la ansiedad (por ser abandonado) y la evitación (de la intimidad). Nuestros resultados sugieren que los adolescentes sufren poca ansiedad por el apego durante la adolescencia, pero informan una evitación del apego más significativa hacia sus padres. La varianza en la calidad de las relaciones de apego de los adolescentes estuvo determinada principalmente por las características del adolescente y por las adaptaciones únicas que hace a la figura de apego. 摘要: 虽然幼儿阶段的依恋几乎完全由父母的行为决定，但青春期的依恋其质量的差异似乎更强烈地受到青少年自身内部的工作模式和所处环境两者之间复杂的相互作用的影响。为了弄清楚导致青少年依恋关系之差异的各种不同的来源，我们运用了社会关系模型。研究对象来自70个相对正常家庭，每位家庭都有两位父母和两位青少年参与研究，他们报告了他们在家庭环境中的依恋关系。本研究将依恋定义为两个不同维度，即焦虑(因为被忽视)和回避(亲密)。本研究结果表明，青少年在整个青春期很少经历依恋焦虑，但他们对父母回避与其亲密依恋关系倒是明显得多。青少年依恋关系在质量方面的差异主要由青少年自身的特点及其对他们依恋的人所作出的独别的调整决定的。